Influence of Interference Fit on Dynamic Characteristics of TBM Cutter Bearing - Defang Zou; Hanqi Yu; Peng Zhou; Zinan Wang; Dan Li (Journal of Engineering)
Bearing interference fits have a significant effect on the cutting characteristics of TBM cutters. In this paper, first, the base interference fit was calculated to select a reasonable tolerance fit. A TBM cutter bearing dynamics model was established by considering the influencing factors, such as bearing interference fit and thermal displacement. Second, the variations in the thermal displacement and stiffness with increasing load were analyzed. Last, the simulation was analyzed via the phase trajectory and Poincaré methods. Time–frequency domain analysis was used to explore the optimum value of the bearing interference fit. The results show that the bearing stiffness tends to increase nonlinearly with the amount of interference fit. In addition, temperature has a significant effect on the thermal displacement of bearings. When the load increased from 2000 to 8000 N, the change in interference caused by thermal displacement increased from 4.45 to 8.61 μm. The maximum error between experiment and simulation is 7.08%, which verifies the reliability of the model. The investigation of the TBM cutter bearing interference fit facilitates analysis of the vibration characteristics of the cutter during the heavy-duty cutting process.